ANALISIS NILAI KEARIFAN LOKAL PADA KUMPULAN CERPEN ROKAT TASE' KARYA MUNA MASYARI DAN PEMANFAATANNYA SEBAGAI BAHAN AJAR MENULIS CERPEN SMA KELAS XI - Lestari Kusuma Dewi, - (2021)
Penelitian ini dilatarbelakangi oleh minimnya ketersediaan bahan ajar dan kurangnya ketertarikan siswa terhadap pembelajaran sastra, khususnya penulisan cerita pendek. Oleh karena itu, peneliti tertarik menyusun rancangan e-modul menulis cerpen kelas XI bertema kearifan lokal. Rancangan e-modul dapat dijadikan panduan untuk siswa merangsang inspirasi dari hal-hal terdekat yang berkembang di masyarakat. Tujuan penelitian ini, yaitu 1) mendeskripsikan struktur cerita; 2) mendeskripsikan nilai kearifan lokal; 3) mendeskripsikan tingkat kesesuaian cerpen dengan kriteria pemilihan bahan ajar di SMA; 4) mendeskripsikan rancangan e-modul bertema kearifan lokal. Metode yang digunakan dalam penelitian ini adalah deskriptif analitik. Berdasarkan hasil analisis dapat disimpulkan beberapa hal: 1) Secara umum, alur yang digunakan memiliki hubungan sebab akibat dengan pengaluran campuran yang memuat realita fiktif, bayangan, dan ingatan. Tokoh dalam cerpen berkisar 4-5 tokoh. Latar waktu memuat waktu bagian hari, minggu, bulan dan tahun. Latar tempat dalam beberapa cerpen merupakan tempat yang ada di Madura. Latar sosial dalam cerpen menunjukkan kepercayaan, kebudayaan, dan aktivitas masyarakat Madura. Gaya penceritaan menggunakan pencerita ekstern dengan sudut pandang orang ketiga mahatahu. Gaya bahasa yang ditemukan, yaitu hiperbola, anafora, personifikasi, paradoks, repetisi, ironi, dan epifora. 2) Nilai kearifan lokal dalam cerpen memiliki keterkaitan yang erat dengan kepercayaan, kebudayaan, dan aktivitas masyarakat Madura dalam dunia nyata. 3) Berdasarkan hasil analisis kesesuaian cerpen terhadap kriteria pemilihan bahan ajar SMA, kelima cerpen termasuk kriteria sesuai. 4) Rancangan e-modul memanfaatkan hasil analisis nilai kearifan lokal yang akan dimuat dalam isi e-modul pada materi dalam dua kegiatan pembelajaran. This research is motivated by a lack of teaching materials and a lack of student interest in learning literature, especially short story writing. As a consequence, researchers are interested in developing an e-module design for writing short stories for students in classes XI on the theme of local wisdom. The design of the e-module can be a guide to students stimulate inspiration from the closest things that develop in society. The objectives of this study are 1) to describe the structure of the story; 2) describe the value of local wisdom 3) describe the suitability of short stories with the criteria for selecting teaching materials in high school; 4) describe the design of e-module with the theme of local wisdom. The method used in this research is descriptive analytic. Based on the results of the analysis, it can be concluded several things: 1) In general, the plot used has a causal relationship with a mixed plot that contains fictitious reality, images, and memories. The characters in the short story range from 4-5 characters. The time setting contains the time of day, week, month, and year. The setting in some short stories is a place in Madura. The social setting in the short story shows the beliefs, culture, and activities of the Madurese community. The storytelling style uses an external narrator from an omniscient third person point of view. The language styles found are hyperbole, anaphora, personification, paradox, repetition, irony, and epiphora. 2) The value of local wisdom in short stories has a close relationship with the beliefs, culture, and activities of the Madurese community in the real world. 3) Based on the results of the analysis of the suitability of short stories against the criteria for selecting high school teaching materials, the five short stories are included in the appropriate criteria. 4) The design of the e-module utilizes the results of the analysis of the value of local wisdom which will be included in the contents of the e-module in the material in two learning activities. The method used in this research is descriptive analytic. Based on the results of the analysis, it can be concluded several things: 1) In general, the plot used has a causal relationship with a mixed plot that contains fictitious reality, images, and memories. The characters in the short story range from 4-5 characters. The time setting contains the time of day, week, month, and year. The setting in some short stories is a place in Madura. The social setting in the short story shows the beliefs, culture, and activities of the Madura community. The storytelling style uses an external narrator from an omniscient third person point of view. The language styles found are hyperbole, anaphora, personification, paradox, repetition, irony, and epiphora. 2) The value of local wisdom in short stories has a close relationship with the beliefs, culture, and activities of the Madurese community in the real world. 3) Based on the results of the analysis of the suitability of short stories against the criteria for selecting high school teaching materials, the five short stories are included in the appropriate criteria. 4) The design of the e-module utilizes the results of the analysis of the value of local wisdom which will be included in the contents of the e-module in the material in two learning activities.